2014
DOI: 10.2527/jas.2013-7130
|View full text |Cite
|
Sign up to set email alerts
|

Effect of essential fatty acid and zinc supplementation during pregnancy on birth intervals, neonatal piglet brain myelination, stillbirth, and preweaning mortality1,2

Abstract: Omega fatty acids and zinc contribute to physiological pathways that could affect the farrowing process, stillbirth, preweaning mortality, and postweaning return to estrus. To determine effects of omega fatty acids and zinc on these reproductive traits, gilts were mated and fed either a control diet, a diet supplemented with 1.09% Gromega, a diet supplemented with 0.07% zinc sulfate, or a diet supplemented with both Gromega and zinc sulfate from d 80 of gestation until farrowing. Farrowings were video recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 43 publications
1
15
0
2
Order By: Relevance
“…Creatine supplementation to sows to maintain ATP supply during strenuous activities in the last 5 d of gestation had no effect on SR (Vallet et al, 2013). Supplementation of essential fatty acids and zinc during the last 35 d of gestation had no impact on SR, whereas zinc supplementation decreased the SR only during prolonged farrowings (Vallet et al, 2014). Likewise, supplementing sows with n-3 long chain polyunsaturated fatty acids from day 60 (Smit et al, 2013) or 107 (Smits et al, 2011) of gestation until farrowing did not affect the SR.…”
Section: Impact Of Energy Status During Farrowing On the Fk Fa And Srmentioning
confidence: 89%
“…Creatine supplementation to sows to maintain ATP supply during strenuous activities in the last 5 d of gestation had no effect on SR (Vallet et al, 2013). Supplementation of essential fatty acids and zinc during the last 35 d of gestation had no impact on SR, whereas zinc supplementation decreased the SR only during prolonged farrowings (Vallet et al, 2014). Likewise, supplementing sows with n-3 long chain polyunsaturated fatty acids from day 60 (Smit et al, 2013) or 107 (Smits et al, 2011) of gestation until farrowing did not affect the SR.…”
Section: Impact Of Energy Status During Farrowing On the Fk Fa And Srmentioning
confidence: 89%
“…They reported fewer abnormal pigs per litter and almost an additional pig per litter when sows were supplemented with 500 ppm compared to 50 ppm Zn. When 700 ppm Zn sulfate was fed from day 80 of gestation until farrowing, stillbirth rate was decreased during prolonged farrowing [ 121 ].…”
Section: Zincmentioning
confidence: 99%
“…Carbonic anhydrase catalyzes the formation of carbonate ion from CO 2 , and is a major mechanism enabling the safe transport in serum of CO2 away from tissues after it is produced. Interestingly, a recent study indicated that supplementation of zinc during late pregnancy reduced the incidence of stillbirths in low birth weight piglets, reinforcing the importance of zinc to the developing pig fetus [ 97 ].…”
Section: Introductionmentioning
confidence: 99%